2014
DOI: 10.1016/j.febslet.2014.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Fe deficiency induces phosphorylation and translocation of Lhcb1 in barley thylakoid membranes

Abstract: a b s t r a c tHvLhcb1 a major light-harvesting chlorophyll a/b-binding protein in barley, is a critical player in sustainable growth under Fe deficiency. Here, we demonstrate that Fe deficiency induces phosphorylation of HvLhcb1 proteins leading to their migration from grana stacks to stroma thylakoid membranes. HvLhcb1 remained phosphorylated even in the dark and apparently independently of state transition, which represents a mechanism for short-term acclimation. Our data suggest that the constitutive phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Depending on the stressing cause, the presence and number of PGs vary, as well as their association with and connection to thylakoid membranes [63]. PGs have been related to stresses, like high light, Fe-deficiency, salt concentration, and heavy metals [64,65,66]. In the present study, PGs were present in both leaf and root cells of plants from all treatments and displayed different types of structures assorted distinctly between the treatments and might be related to diverse functions or degree of maturation (Figure 5A–C green arrows and yellow arrowheads) [63,67].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the stressing cause, the presence and number of PGs vary, as well as their association with and connection to thylakoid membranes [63]. PGs have been related to stresses, like high light, Fe-deficiency, salt concentration, and heavy metals [64,65,66]. In the present study, PGs were present in both leaf and root cells of plants from all treatments and displayed different types of structures assorted distinctly between the treatments and might be related to diverse functions or degree of maturation (Figure 5A–C green arrows and yellow arrowheads) [63,67].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, in addition to Thr 23, other phosphorylation sites of LHCB1 were all downregulated in the yellow sectors (Figure 9A). Studies have shown that the phosphorylation of LHCB1 is essential for optimizing the photosystem balance under changing environments [25,26]. The different phosphorylation sites of LHCB1 might play different roles in energy balance (Figure 9A).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prolonged Fe-deficiency (more than two weeks) induces non-photochemical quenching (NPQ), in which the excess-absorbed light energy is dissipated into heat, with the phosphorylation and monomerization of HvLhcb1, a major light-harvesting antenna protein of PSII. This NPQ induction results in protection from the photo-inhibitory effect caused by Fe-deficiency [13,18]. We propose that these features allow barley to sustain photosynthesis under long-term Fe-deficient conditions.…”
Section: Introductionmentioning
confidence: 87%